Digital Platforms and Art Practice: Innovative Paradigm Shift for Nigerian Visual Artists - Eseagwu, Oyenike O.; Ekeamadi, Alexander K. (NIU Journal of Humanities, 2024)
The delay in the sale of artworks due to various factors presents a significant challenge for art practice in Nigeria. With both local and global exhibitions taking place, many artists find themselves with unsold works accumulating in their studios, galleries and storage spaces. This issue represents not only a waste of time, materials and energy but also results in the inefficient use of valuable space. While some artists have turned to digital platforms as a means to market and sell these works, they face additional obstacles, such as the difficulty in protecting their original concepts, further delays and the high commissions charged by third-party websites that facilitate sales. This paper examines the extent to which digital platforms are being utilized by studio artists and visual art students in Nigeria. A mixed-method research design, integrating quantitative and qualitative approaches, to investigate these challenges are employed. Data was collected through surveys from 50 studio artists and visual art students in Nigeria, using purposive sampling. The findings indicate that although most local artists are yet to explore digital platforms for art sales, younger studio artists and art students, particularly those in tertiary institutions, are more inclined to explore digital platforms for merchandising their works. The study concludes that as digital technologies gain wider acceptance in art practice and merchandise, there is a pressing need for visual art institutions, prominent art galleries and professional bodies to establish their own websites. Such initiatives could reduce the reliance on middlemen, lower commission charges and enhance visibility for artists, thereby fostering better connections with art collectors and patrons to boost sales. The study highlights the importance of digital marketing skills for all categories of studio artists and art students, emphasizing that proficiency in these areas is crucial for navigating the evolving art market and ensuring the sustainable commercialization of their works. Keywords: Digital platforms, art practice, visual art, innovative paradigm shift.